2016
DOI: 10.1128/aac.02813-15
|View full text |Cite
|
Sign up to set email alerts
|

The LABCG2 Transporter from the Protozoan Parasite Leishmania Is Involved in Antimony Resistance

Abstract: Treatment for leishmaniasis, which is caused by Leishmania protozoan parasites, currently relies on a reduced arsenal of drugs. However, the significant increase in the incidence of drug therapeutic failure and the growing resistance to first-line drugs like antimonials in some areas of Northern India and Nepal limit the control of this parasitic disease. Understanding the molecular mechanisms of resistance in Leishmania is now a matter of urgency to optimize drugs used and to identify novel drug targets to bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 46 publications
(63 reference statements)
0
45
1
Order By: Relevance
“…The overexpressing LABCG2 reduced accumulation of Sb III due to an increased in drug efflux [3]. Due to the toxicity and the failure of many drugs available, the search for alternative therapies for leishmaniasis is urgent.…”
Section: Leishmaniasis Is Caused By the Protozoanmentioning
confidence: 99%
“…The overexpressing LABCG2 reduced accumulation of Sb III due to an increased in drug efflux [3]. Due to the toxicity and the failure of many drugs available, the search for alternative therapies for leishmaniasis is urgent.…”
Section: Leishmaniasis Is Caused By the Protozoanmentioning
confidence: 99%
“…Additionally, biotinylation assays suggested that part of the protein is localized in the PM, where the transporter could interact with other PM transporters involved in antimony uptake, such as aquaglyceroporin (AQP1). Two ABC transporters Antimicrobial Agents and Chemotherapy described by our group, ABCI4 and ABCG2, also showed a dual localization and played a role in Sb III resistance (8,9). Several other eukaryotic ABC transporters are found in mitochondria, and most of them belong to the B subfamily of ABC transporters (40).…”
Section: Discussionmentioning
confidence: 93%
“…Considering that some ABC transporters have been implicated in drug resistance in Leishmania (8,9,17,29), we decided to analyze whether the overexpression or partial knockout of ABCI3 could confer resistance to drugs and other related molecules. Different leishmanicidal drugs, including antimonials (Sb III ), miltefosine, amphotericin B, and paromomycin, were tested, as was As III , a metal ion which has been shown to be cross-resistant to Sb III (30); Zn-protoporphyrin, a toxic porphyrin and validated heme analog (8); and H 2 O 2 , a by-product of superoxide radical formation during macrophage activation (31) ( Table 1).…”
Section: Abci3 Involvement In Leishmania Antimony Susceptibilitymentioning
confidence: 99%
See 2 more Smart Citations